0236 Associations of Media Use and Nocturnal Sleep Duration Among US Adolescents: Mediating Effects of Chronotype. (12th April 2019) - Haynie, Denise L; Maultsyby, Katherine; Lewin, Daniel; Lipsky, Leah; Sundaram, Rajeshwari; Simons-Morton, Bruce
Abstract: Introduction: Media use may shorten the sleep period among adolescents, particularly later chronotypes. We investigated cross-sectional and longitudinal associations of time spent on gaming, social media, and television/DVDs with scheduled- and free-day sleep duration, and examined chronotype as mediating these relations. Methods: Data drawn from the NEXT Generation Health Study's first 3-waves (W1-W3, 10 th -12 th grade, n=2520) and 7 th -wave (W7, 4-years post-high school) were used in path models (MPlus V7.4). W3 and W7 scheduled- and free-day sleep durations were calculated from participant reports of usual wake- and sleep-time. Chronotype was extrapolated from the adjusted free-day sleep period midpoint. Media use was assessed as average hours/day on each platform. Latent variables (W1-W3) were constructed for media use and chronotype. Models evaluated chronotype as mediating relations between each type of media use and sleep duration. Results: Social media was directly associated with W3 scheduled-day sleep duration (-0.09, p<.0001); the path between chronotype and duration was attenuated to non-significance. Results for W3 free-day sleep duration indicated a significant direct effect for TV (0.12, p=.004) and indirect effects for gaming (-0.04, p=0.03), social media (-0.05, p=0.017), and TV (-0.04, p=.012). In prospective analyses, social media had a direct effect (0.07, p=0.01) on W7 free-day sleep duration. In W7 cross-sectional analyses, significant direct (game 0.07, p=0.03; social media -0.05, p=0.04) and indirect effects (game 0.03, p=0.01; social media 0.02, p<.0001; TV 0.02, p=02) were found for scheduled-day sleep duration. For W7 free-day duration, indirect effects were obtained (gaming -0.03. p=0.003; social media -0.02, p=0.01; TV -0.02, p=.01). Conclusion: Results suggest that chronotype mediates associations between sleep duration and media use. Later chronotype, typical of adolescents, contributes to short sleep duration. Social media may be a high value intervention target during high school. Longitudinal results suggest high school media use patterns may not carry over into early adulthood, although concurrent media use is related to shorter sleep duration at older ages. Support (If Any): This research (contract #HHSN275201200001I) was supported by the Intramural Research Program of NICHD, and NHLBI, NIAAA, NIDA, and HRSA.